Biodiesel production : technologies, challenges, and future prospects - Tyagi, R. D., 1952- (American Society of Civil Engineers, 2019)
Biodiesel Production: Technologies, Challenges, and Future Prospectsprovides in-depth information on fundamentals, approaches, technologies, source materials and associated socio-economic and political impacts of biodiesel production.